2003
DOI: 10.1086/378288
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Afterglows of Four Gamma‐Ray Bursts: Constraining the Explosion and Fireball Model

Abstract: We employ a fireball model of the gamma-ray burst explosion to constrain intrinsic and environmental parameters of four events with good broadband afterglow data; GRB 970508, GRB 980329, GRB 980703, and GRB 000926. Using the standard assumptions of constant circumburst density and no evolution of the fraction of the explosion energy in the post-shock magnetic field, we investigate the uniformity of the derived explosion and shock physics parameters among these events. We find a variety of parameters: densities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
347
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(392 citation statements)
references
References 76 publications
43
347
2
Order By: Relevance
“…These values are similar to those obtained for GRBs at z∼1 (Panaitescu & Kumar 2002;Yost et al 2003;Chandra et al 2008;Cenko et al 2010Cenko et al , 2011Laskar et al 2014), indicating no evolution in these properties with a redshift to z∼5.…”
Section: Summary and Discussionsupporting
confidence: 85%
“…These values are similar to those obtained for GRBs at z∼1 (Panaitescu & Kumar 2002;Yost et al 2003;Chandra et al 2008;Cenko et al 2010Cenko et al , 2011Laskar et al 2014), indicating no evolution in these properties with a redshift to z∼5.…”
Section: Summary and Discussionsupporting
confidence: 85%
“…There is a growing number of studies which have modelled broad-band GRB light curves, and these have yielded results for B which span several orders of magnitude between different GRBs, with values from ∼10 −5 to ∼10 −1 (Panaitescu & Kumar 2001, 2002Yost et al 2003), raising questions whether the assumption of B being constant in the simplest fireball model is consistent with the observations. Lately, the idea of B increasing in time as a power-law has been discussed and is receiving increasing support from observational data (e.g., Panaitescu et al 2006;Kong et al 2010).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The possibility of non-constant equipartition parameters has been considered by Chevalier (2003) and used in afterglow modelling by Yost et al (2003) who assumed that α B varies with the shock Lorentz factor. For the prompt phase, have shown that the condition 2x + y < 1 (which therefore excludes the standard values x = 1/2 and y = 5/2) is often required to obtain good fits of the temporal and spectral evolution of GRB pulses.…”
Section: A Toy Model For Internal Shocksmentioning
confidence: 99%